Postprandial Increase of Complement Component 3 in Normolipidemic Patients With Coronary Artery Disease: Effects of Expanded-Dose Simvastatin - Halkes, C.J.M.; van Dijk, H.; de Jaegere, P.P.T.; Plokker, H.W.M.; van derHelm, Y.; Erkelens, D. W.; Castro Cabezas, M. (Arteriosclerosis, thrombosis, and vascular biology, 2001)
Plasma concentrations of the third complement component (C3) predict the risk of myocardial infarction. Because chylomicrons stimulate C3 production by adipocytes in vitro, we investigated plasma C3 changes in vivo after an oral fat load. Thirty-seven subjects (20 normolipidemic patients with coronary artery disease [CAD] and 17 healthy control subjects) underwent an oral fat load (50 g/m). C3 was measured at baseline and at 2-hour intervals after fat intake for 10 hours. The effects of lipid lowering by simvastatin were evaluated in 16 patients. Fasting plasma C3 was 1.06±0.26 and 0.90±0.12 g/L in CAD patients and control subjects, respectively. Fasting C3 was correlated with several parameters associated with insulin resistance. The best determinant of fasting C3 was waist circumference (adjusted R=0.48, β=0.71, P <0.001); the addition of postprandial triglyceridemia to the model improved it (adjusted R=0.63). Plasma C3 levels at 2, 4, and 6 hours after fat ingestion were significantly higher than fasting levels in patients and control subjects. C3 increased maximally to 1.39±0.33 g/L in patients and to 1.11±0.18 g/L in control subjects (P <0.01 for patients versus control subjects). Total postprandial triglyceridemia was the best determinant of maximal C3 increase (adjusted R=0.47, β=0.70;P <0.001). Treatment with simvastatin decreased fasting and postprandial C3 by 6% and 39%, respectively (P <0.05 for both versus no treatment). Postprandial plasma C3 concentrations increase in CAD patients and control subjects. Fasting C3 is associated with waist circumference, but postprandial C3 increment is associated with postprandial lipemia. Fasting and postprandial C3 concentrations decrease after treatment with simvastatin.